2002
DOI: 10.1046/j.1439-0469.2002.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of populations of Iberian rock-lizards Iberolacerta (Iberolacerta) sensuArribas (1999)

Abstract: The genetic structure and relationships of five populations of the Iberian group of Iberolacerta (sensuArribas 1999) were analysed by protein electrophoresis. In this study we confirmed the differentiation between the group of populations from Galicia/Cantabrian/S. Estrela versus the group of populations from de Spanish Central System, Gredos and Guadarrama that are included in the two different species by Arribas (Herpetozoa 9(1/2), 31–56, 1996; Russian J. Herpetol. 6, 1–22, 1999), Iberolacerta (I.) monticola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…According to this hypothesis, Serra da Estrela would have acted as a Pleistocene refuge from which a rapid range expansion of I. monticola would have probably occurred after the end of the Würm glacial period. This interpretation is coherent with the climatic conditions during the Quaternary and is also in agreement with biogeographical scenarios proposed for other reptiles and amphibians around the same general area: Chioglossa lusitanica (Alexandrino et al 1997(Alexandrino et al , 2000; Lacerta schreiberi (Gordinho et al 2002(Gordinho et al , 2003Paulo et al 2001Paulo et al , 2002 and Podarcis (Pinho et al 2002).…”
Section: Discussionsupporting
confidence: 84%
“…According to this hypothesis, Serra da Estrela would have acted as a Pleistocene refuge from which a rapid range expansion of I. monticola would have probably occurred after the end of the Würm glacial period. This interpretation is coherent with the climatic conditions during the Quaternary and is also in agreement with biogeographical scenarios proposed for other reptiles and amphibians around the same general area: Chioglossa lusitanica (Alexandrino et al 1997(Alexandrino et al , 2000; Lacerta schreiberi (Gordinho et al 2002(Gordinho et al , 2003Paulo et al 2001Paulo et al , 2002 and Podarcis (Pinho et al 2002).…”
Section: Discussionsupporting
confidence: 84%
“…In contrast with its af nity for mountains, it is also found at sea level, from altitudes of 0 to 400-500 m on the damp, north-facing slopes and deep river valleys in the north of Galicia and west of Asturias, north-west Spain (Elvira and Vigal, 1982;Galán, 1982;Pérez-Mellado, 1997, 1998, 2002. Recent studies found an unexpectedly close genetic similarity between the populations of Galicia and the Serra da Estrela, as well as a considerable genetic differentiation between the Galician and Cantabrian populations, both included in the same subspecies, L. monticola cantabrica (Almeida et al, 2001).…”
Section: Study Speciesmentioning
confidence: 99%
“…The observed heterozygosity found in A. bedriagae (Ho = 0.092) is higher than the average values (but included within the range) calculated for 17 species of lacertid lizards belonging to the same tribe of A. bedriagae (i.e. Lacertini Oppel, 1811) (Ho = 0.059; Gorman et al, 1975;Cirer & Guillaume, 1986;Busack, 1987;Capula, 1994aCapula, , 1996Capula, , 1997Capula, , 2004Fu et al, 1995;MacCulloch et al, 1995MacCulloch et al, , 1997Brehm et al, 2001;Almeida et al, 2002;Capula & Ceccarelli, 2003). The average observed heterozygosity of Corsican populations is similar to that of Sardinian populations.…”
Section: Discussionmentioning
confidence: 55%